A Review of Social Media and Implications for the Sales Process - Andzulis, James "Mick"; Panagopoulos, Nikolaos G.; Rapp, Adam (The Journal of personal selling & sales management, 2012)
Technology-based research has a long, storied history in the sales discipline. Beginning with the role of computers to laptops, moving to the influence of the Internet, onward to customer relationship management and sales force automation applications, and now to the role of social media, sales research is being shuttled into a new technological paradigm. The purpose of this paper is to review the role of social media in the sales force and the sales process. We begin the paper by providing definitions of social media and reviewing the role and importance of social media in business. An analogy between the rise of Internet usage in the sales force and the advent of social media is presented and discussed. Next, we discuss the challenges of social media in the sales and marketing interface and review four different business strategies to determine who "owns" social media within an organization. We continue with a discussion of the different stages in the sales process and offer ways in which social media influences each individual step, thereby outlining future research opportunities.